Climate-smart crop production can support household food and nutrition security in urban communities in Chitungwiza, Zimbabwe - Nyamasoka-Magonziwa, Blessing; Simango, Esther; Nezomba, Hatirarami (Frontiers in Agronomy, 2025)
IntroductionGlobal environmental change, including climate change, has adversely affected urban smallholder farmers in producing adequate and nutritious food to meet household needs in developing countries. Adopting climate-smart agriculture (CSA) practices can contribute to mitigating this challenge.MethodsA study was carried out to evaluate current climate-smart crop production practices by urban farmers in Chitungwiza District, Zimbabwe, and their effects on household diets. Mixed methods research using a convergent parallel design was carried out where focus group discussions were carried out with four groups of farmers of diverse composition; and 107 households were randomly selected and interviewed in 2022. Farmers were grouped as climate-smart (CS) and non-climate-smart (non-CS) based on cropping sequences, soil fertility management practices, seed selection, soil water management, and tillage practices using a matrix.ResultsResults showed that only 23% of the farmers were classified as climate-smart. The adoption of climate-smart practices was influenced by the socio-economic status of the farmers i.e., age-influenced type of seed grown (p<0.05); employment status influenced tillage method used (p=0.04) as well as water management practices (p=0.04), and education level influenced the cropping system (monocropping versus diversified; p=0.03). There were no significant differences in maize yield of CS and non-CS farmers, with CS farmers having an average maize yield of 2.10t/ha vs. 2.27 t/ha, respectively, in the 2020/2021 season. Climate-smart crop production had a positive influence on household diets with CS households having a significantly higher Household Dietary Diversity Score (HDDS) than that of non-CS farmers (3.3 vs. 2.9; p=0.02).DiscussionWe concluded that the adoption of climate smart agronomic practices in urban agriculture positively impacts food and nutritional outcomes for urban communities thus contributing to the United Nations Sustainable Development Goal 2 of reducing hunger and poverty by year 2030.